(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article is devoted to a comparative study of phraseological units with the semantics of "wealth-boylik" in the Uzbek language. The study analyses how the concept of wealth is expressed in various linguistic units, as well as its linguacultural and figurative features. The analysis revealed symmetrical aspects of phraseological units - semantic content, metaphorical imagery, and functional similarities and asymmetrical aspects - differences related to national mentality, cultural values, and social context. The results of the article will be useful for translation and linguacultural studies.